Effects of colour and scene dynamism on visual fatigue in animated films - Marc Argilés; Elisabet Fonts; Luis Pérez-Mañá; Beatriz Martinez-Navarro; Carles Sora-Domenjó; Elisabet Pérez-Cabré; Bernat Sunyer-Grau; Cristina Rovira-Gay; Carla Molins-Pitarch; Lluïsa Quevedo-Junyent (Scientific Reports)
Abstract Animated films are highly popular in society, particularly among children and adolescents. During film production, selecting an adequate colour palette and scene dynamism is crucial for creating a visual impact on the audience. However, the influence of visual aesthetics, such as colour and scene dynamism on visual fatigue remains unexplored. In the present study, visual fatigue was assessed and compared in 30 young participants after viewing two popular films: Spider-Man: Across the Spider-Verse, an active, fast-paced film, and My Neighbour Totoro, a more relaxed film. Both films were viewed twice, once with the original colour palette and once in greyscale. Watching Spider-Man film induced a greater degree of visual fatigue than My Neighbour Totoro in two subjective questionnaires evaluating visual fatigue, and in the vergence facility and binocular accommodative facility tests. Moreover, important differences in the visual dynamics and colour aspects between both films were found. These results demonstrate that the high-paced and high-colour aspects of films directly affect visual fatigue. Future animated film producers should consider these factors that are relevant to their audiences.